Balancing Usability and Security in Secure System Design: A Comprehensive Study on Principles, Implementation, and Impact on Usability - Agboola, Taofeek Olayinka; Adegede, Job; Jacob, John G. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose - The purpose of this study is to provide a comprehensive analysis of the principles and implementation strategies of secure system design, emphasizing the critical balance between security and usability. This study aims to uncover how usability impacts the effectiveness of secure systems, exploring the human-centric approach to security. This research offers insights for organizations to develop systems that ensure robust security while providing a seamless, intuitive user experience. Method - This study employs an extensive review of existing literature on secure system design principles, usability studies, and human-centric security approaches. Result - Identification of fundamental principles that underpin secure system design, like confidentiality, integrity, availability, authentication, and authorization. Highlights common usability challenge; including complex authentication processes, poor interface design, and lack of user-friendly features. Examining the necessary trade-offs and providing strategies to achieve a balance between robust security measures and user convenience. Conclusion – The study concludes that secure system design must adopt a human-centric approach, emphasizing usability's role in effective security. Technical measures are vital, but user behavior significantly impacts overall security. Addressing usability challenges enhances compliance and reduces risks. Integrating security and usability principles is essential for developing secure, user-friendly systems  Recommendation – Future research should focus on user-centered design for secure systems, incorporating continuous usability testing to promptly address issues. Provide comprehensive user education to enhance security awareness. Encourage collaboration between designers and security experts to create solutions that balance security and usability effectively. Research Implication - The research highlights the critical link between usability and security in system design, underscoring the need for a human-centric approach. It provides guidelines for creating secure, user-friendly systems to boost compliance and reduce risks, while also informing policy and encouraging further exploration of balancing security and usability in technology.